Quantification of cytosolic interactions identifies Ede1 oligomers as key organizers of endocytosis - Böke, Dominik; Trautmann-Hoenicke, Susanne; Meurer, Matthias; Wachsmuth, Malte; Godlee, Camilla; Knop, Michael (Molecular systems biology, 2014)
Clathrin-mediated endocytosis is a highly conserved intracellular trafficking pathway that depends on dynamic protein-protein interactions between up to 60 different proteins. However, little is known about the spatio-temporal regulation of these interactions. Using fluorescence (cross)-correlation spectroscopy in yeast, we tested 41 previously reported interactions in vivo and found 16 to exist in the cytoplasm. These detected cytoplasmic interactions included the self-interaction of Ede1, homolog of mammalian Eps15. Ede1 is the crucial scaffold for the organization of the early stages of endocytosis. We show that oligomerization of Ede1 through its central coiled coil domain is necessary for its localization to the endocytic site and we link the oligomerization of Ede1 to its function in locally concentrating endocytic adaptors and organizing the endocytic machinery. Our study sheds light on the importance of the regulation of protein-protein interactions in the cytoplasm for the assembly of the endocytic machinery in vivo.